HARMONIZATION OF INVESTMENT BUSINESS SECTOR REGULATIONS (LAW NO. 11 OF 2020 AND PRESIDENTIAL REGULATION NO. 49 OF 2021) - Saleh Seff, Alfarisi Hamdani (Fakultas Hukum Universitas Djuanda, 2024)
The investment business sector in Indonesia, both local and foreign, is actually regulated in Law no. 11 of 2020 concerning Job Creation which amends some of the contents of Law Number 25 of 2007 concerning Capital Investment and Presidential Regulation Number 49 of 2021. The aim of this research is to find out whether the two regulations are harmonious and which regulations are will be used as a reference if disharmonization occurs. This research uses a type of normative research or what is usually called doctrinal research. The research results show that the two regulations are harmonized and if disharmonization occurs, then Law no. 11 of 2020 which will be used as a reference.